Life in Christ: Eastern Perspectives on Christian Ethics - Kalluveettil, Paul (Asian Horizons, 2011)
Paulachan P. Kochappilly, Life in Christ: Eastern Perspectives on Christian Ethics, Bangalore: Dharmaram Publications, 2010. Pages: xvi+273. ISBN: 978-81-89958-34-3